Marketing Strategy of "Kopi Gunungan" (KUB) Putra Bumi Nusantara in Sawo Village, Dukun District, Gresik Regency - Rif'al Ulum Zidn; Nurul Badriyah; Titin Titin (Jurnal Price : Ekonomi dan Akuntasi, 2025)
This study aims to find out how the marketing strategy carried out by KUB Putra Bumi Nusantara in Increasing Gunungan Coffee Sales. This study uses a qualitative descriptive method with SWOT analysis to seize opportunities and maximize strengths, reduce weaknesses and avoid threats. From the results of this research SWOT analysis, it can be seen that KUB Putra Bumi Nusantara is running an SO (Strenght Opportunity) strategy, which is a strategy where the organization uses its strengths and opportunities to run its business.